Ekspansi Hindia Belanda dan Runtuhnya Kekuasaan Elit Tradisional Kerajaan Koto Besar di Rantau Batanghari - Romi Arif; N. Nopriyasman; Mhd. Nur (HISTORIA : Jurnal Program Studi Pendidikan Sejarah, 2020)
This study discusses about expansion of the Dutch Indies Government in the area Kingdom of Koto Besar, which is a cow instead the Kingdom of Pagaruyung. This research was conducted using historical science methods and social science approaches as a tool. The first stage of this research, namely the collection of data carried out with literature and field studies. After the data is collected, it continues with source criticism in obtaining historical facts. Furthermore, these facts are interpreted, until closed with historiography (writing). The results of this study revealed that there was a relationship between the arrival of the Dutch East Indies and the collapse of the power of the traditional elite in the Kingdom of Koto Besar. At first the Dutch only asked permission from Tuanku Koto Besar to place troops in his territory. In its development, it turned out that the Netherlands had another purpose, which was to fully control the Koto Besar region. This has an impact on the power of traditional elites who have long had influence in the Koto Besar Kingdom.